Integrasi Netiquette dan Resiliensi Digital sebagai Strategi Preventif Cyberbullying pada Remaja Awal di Era Disrupsi Teknologi - Noor Afy Shovmayanti; Ardiansyah Ardiansyah (Universitas Tidar, 2025)
This study aims to analyze the integration of internet etiquette and digital resilience as a preventive strategy against cyberbullying among adolescents in the era of technological disruption. A qualitative descriptive-exploratory approach was employed, involving 56 elementary school students, teachers, and parents through questionnaires, semi-structured interviews, and thematic analysis. The findings reveal that students’ understanding of digital ethics is relatively high, with 92.8% reporting consistent application of ethical online behavior. However, digital resilience remains limited, as 69% of students feel lonely without social media and 57% are easily influenced by negative comments. Cyberbullying experiences were reported by 30.8% of respondents, with most adopting passive responses. These results highlight the urgency of digital literacy programs that emphasize not only courtesy and privacy but also emotional management, healthy communication, and coping skills in digital interactions. Integrating internet etiquette and digital resilience can foster an ethical, safe, and resilient digital ecosystem for adolescents.